Evaluation of MODIS-Aqua and OLCI Chlorophyll-a products in contrasting waters of the Southwestern Atlantic Ocean - Ana Laura Delgado; Paula Daniela Pratolongo; Ana Inés Dogliotti; Maximiliano Arena; Carla Celleri; John Edison Garzón Cardona; Ana Martinez (Ocean and Coastal Research)
Evaluation of MODIS-Aqua